ENZYMATIC DEINKING OF OLD NEWS PAPER USING CRUDE LACCASE ENZYME FROM MARASMIELLUS PALMIVORUS - Zunaidah, Sitatun
Biodeinking technology is used in the paper industry to remove ink on waste paper. ONP (old newspaper) constitutes an excellent low cost and commonly used in paper recycling. The use of crude laccase extract from Marasmiellus palmivorus in biodeinking has never been observed before. The objective of this research was to determine the potential use of laccase in enzymatic deinking to increase the brightness value (>55% ISO) and reduce ERIC (Effective Residual Ink Concentration) on secondary paper. Laccase was generated from M. palmivorus, using cultivation in a static Solid State Fermentation (SSF) reactor with lignocellulosic as substrate. The methodology involves the production of crude laccase extract, laccase optimization using variations of dosage, temperatures, and times. The potential of crude lacase extract in biodeinking was studied by measuring the brightness value and decreasing ERIC. The results will be analyzed statistically using MANOVA. The highest laccase activity is 1.223,33 U/L (7,55 U/mg). Optimization of laccase crude extract enzyme in biodeinking can increase brightness values by 15,22% (54,27% ISO) to 25,03% (58,89% ISO) compared to controls (47.09% ISO) and reduce ERIC values by 46,12% (452,10 ppm) to 67,89% (269,38 ppm) compared to control (839.15 ppm).